Bridging readiness and reasoning: A mixed methods study on learning readiness and students’ argumentation in mathematics - Fauziyah, Nur; Jamil, Erfina; Khikmiyah, Fatimatul; Edy, Sarwo (Fakultas Tarbiyah Universitas Ibrahimy, 2025)
This study aimed to investigate the relationship between learning readiness and students' argumentation patterns in mathematics learning, and to describe these patterns using Toulmin's argumentation model. Using a mixed-methods approach with a parallel convergent design, this study was conducted in class XI of SMA Negeri 1 Gresik in 5 parallel courses. Subjects were selected through purposive sampling, resulting in three students with different learning readiness levels: advanced, developing, and needing guidance. Data were obtained through tests, think-aloud, and interviews. The data obtained consisted of quantitative and qualitative data. Quantitative data in the form of student argumentation ability scores were subjected to statistical tests to determine their correlation with the level of learning readiness. At the same time, the qualitative data obtained were identified based on Toulmin's argumentation pattern. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion. The results showed a positive correlation between learning readiness and students' argumentation ability in mathematics learning. Additionally, it was found that students with different learning readiness categories exhibited distinct mathematical argumentation patterns. In students with learning readiness who need guidance, the argumentation patterns used are claim, ground, and warrant. Students with developing and advanced learning readiness exhibit argumentation patterns, which include claims, bases, warrants, support, and qualifications. This study differs from previous studies in that learning readiness is measured by the ability to understand prerequisite material, rather than general learning readiness.